Roma capta! – Uwagi na temat relacji o zdobyciu Rzymu w 410 i 455 r. w dziełach wybranych autorów późnoantycznych - Wilczyński, Marek (Vox Patrum, 2018)
In the presented article the author analyses depictions of sieges and captures of Rome in the years 408-410 and 455 passed on by selected authors of Latin and Greek sources from the late antique. The scope of the research included sources containing more extensive narratives, while sources containing only laconic annual information solely about the fact of capturing the city were rejected. In the depictions of the capture of Rome by Alaric in 410 the authors rather tend to seek supernatural reasons, and less often logical explanations of the origin of the events, contrary to the depictions of the year 455, where one can find almost exclusively rational justifications for the course of events, determined by political situation. While discussing the events of the year 410 the authors oftentimes create their own original digressions and allow for deviations from the historic reality. The relations about the year 455 are consistent and show only minor differences. Contrary to later opinions, the capture of Rome in 410 was not considered a gigantic tragedy outside Italy, although it was recognized as a breakthrough moment. For the eastern historians these events are remote, taking place in lands far from Constantinople and often their depiction is used to indicate the superiority of the Eastern Empire over the Western Empire. Sacco di Roma by Genseric in 455, which is referred more precisely and recognized as an element of significant history and politics of the East (Vandals corsair raids, Leo the Thracian’s expedition, recapturing Africa during the reign of Justinian I), is treated in an entirely different manner.